Sistem Aquaponik Dengan Teknik Pasang Surut Dan Teknik NFT Menggunakan Air Media Kolam Lele - Kemala Hadidjah (Buletin Loupe, 2020)
The needs of fish and vegetables always increase according to population growth and the need to improve family nutrition. Aquaponik is one solution to meet the needs of vegetables and fish because it can be done on a household scale. Aquaponik is an integrated cultivation technology between aquaculture and hydroponics techniques. Catfish is easy to cultivate and can be done in household scale. Hydroponics Technique NFT (Nutrient Film Technique) and Tidal have certain characteristics of plants that need to know by comparing the two. It is hoped that this research can give innovation technology of fish and vegetable cultivation that is integrated and easy to do with satisfactory result. The aquaponic system produces total green mustard greens 17.79 kg of mustard which is harvested after 30 days and catfish produced as much as 16.4 kg with the amount of 98 tail so obtained SR 82% and cultivated for 64 days. The making of props Aquaponik System in college especially Polytechnic of Agriculture will give learning of applied technology appropriately in order to increase student knowledge and help teaching material for lecturer. Outcomes from universities are expected to provide a tangible form for the community in the form of technological innovations that can be applied on a simple scale.